PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN (Pada Perusahaan LQ45 yang Terdaftar di Bursa Efek Indonesia) - Kirmizi Ritonga; Jessica Andriyanie (PEKBIS, 2012)
This study examines empirical proof and analyzes the Value Added IntelectualTMCoefficient (VAIC ) for measuring the value-based performance of Indonesian 51corporations listed in Indonesian Stock Exchange which are included in LQ45 forthree years, 2007 to 2009. Annual reports,in terms of profit and loss and balancesheet reports of the corporations included in LQ45 related to the relevant timeperiod, were used to acquire the data target. A review is conducted of internationalliteratures on intelectual capital with specific reference to literature which reviewsTMmeasurement techniques and tools, and the VAIC method is applied to analyzethe data of Indonesian corporations listed in Indonesian Stock Exchange for threeyears of time period. The results of the study were there were the significant effect ofValue Added Capital Employed and Value Added Human Capital on Earning Pershare. Contradict result has been happened in this study that there were not effectof Strutural Capital Value Added on Earning Per Share. It means that whatever thecapital used in the corporations which is not effect on the performance achievedcorporations included on the LQ45.